A Systematic Literature Reviewe of Performance Management of Zakat Funds Institutions on Redistribution of Indonesian Revenue - Afifah, Zainiyatul (IPTEK Journal of Proceedings Series, 2020)
The main purpose of zakat as an Islamic financial instrument that aims as an equal distribution of revenue and maslahah. Indonesia with the Muslimmajority community, has great potential in collecting zakat funds, it is expected to be a solution to the income inequality and poverty in Indonesia. However, the realization of zakat still far from the potential. It is indicate that the performance of zakat fund management institutions has not been maximized.This study aims toreview and organize the performance management of zakat fund institution and organize its impact on income equality and poverty in Indonesia. This study provides a qualitative and critical review of efficiency performance management zakat fund institution and theinfluence on income distribution and poverty alleviation in IndonesiaBy critical review and classifying the result of previous research found some propositions: (1)Management of zakat funds have affect on the performance of zakat institutions (2) the efficiency of the performance management of zakat fund institutions have impact on the equitable distribution of zakat funds (2) the effectiveness distribution of zakat fund institution have a significant affect on poverty alleviation and equitable distribution of income